Influence of graphite tailings on the mechanical performance, of ultra-high performance concrete - Jialun Sun; Ming Sun; Anshuang Su; Xiaojian Gao (Case Studies in Construction Materials)
Graphite tailings (GT), a prevalent solid waste in China, have lacked effective utilization strategies. This paper investigated using GT as a substitute for quartz sand in Ultra-high Performance Concrete (UHPC) to assess its potential for solid waste disposal. In this work, UHPC specimens were prepared with varying GT contents under standard and steam curing conditions. The study evaluated the impact of GT on fluidity, water absorption, and mechanical properties of UHPC. XRD, TG, FTIR, and SEM were used to characterize the types and microstructure of hydration products within UHPC. Results indicate that the increase in GT content reduces the fluidity of UHPC but also decreases the water absorption because the smaller particle size of GT effectively filles the pores. This substitution significantly improves mechanical properties of UHPC under standard curing, with both compressive and flexural strengths peaking at 60 % GT—125 MPa and 26 MPa, respectively. Under steam curing, while flexural strength displays a similar trend, compressive strength continues to increase, reaching up to 150 MPa. Microscopic analysis reveals that GT enhances the hydration reactions and optimizes the pore structure, thus enhancing the mechanical properties of UHPC. These results provide a theoretical basis for the use of GT in UHPC, promoting their broader application and disposal.